GPX3 expression was down-regulated but positively correlated with poor outcome in human cancers - Hu, Qingyi; Chen, Jiaoshun; Yang, Wen; Xu, Ming; Zhou, Jun; Tan, Jie; Huang, Tao (Frontiers in Oncology, 2023)
Introduction Cancer is a crucial public health problem and one of the leading causes of death worldwide. Previous studies have suggested that GPX3 may be involved in cancer metastasis and chemotherapy resistance. However, how GPX3 affects cancer patients’ outcomes and the underlying mechanism remains unclear. Methods Sequencing data and clinical data from TCGA, GTEx, HPA, and CPTAC were used to explore the relationship between GPX3 expression and clinical features. Immunoinfiltration scores were used to assess the relationship between GPX3 and the tumor immune microenvironment. Functional enrichment analysis was used to predict the role of GPX3 in tumors. Gene mutation frequency, methylation level, and histone modification were used to predict the GPX3 expression regulation method. Breast, ovarian, colon, and gastric cancer cells were used to investigate the relationship between GPX3 expression and cancer cell metastasis, proliferation, and chemotherapy sensitivity. Results GPX3 is down-regulated in various tumor tissues, and GPX3 expression level can be used as a marker for cancer diagnosis. However, GPX3 expression is associated with higher stage and lymph node metastasis, as well as poorer prognosis. GPX3 is closely related to thyroid function and antioxidant function, and its expression may be regulated by epigenetic inheritance such as methylation modification or histone modification. In vitro experiments, GPX3 expression is associated with cancer cell sensitivity to oxidant and platinum-based chemotherapy and is involved in tumor metastasis in oxidative environments. Discussion We explored the relationship between GPX3 and clinical features, immune infiltration characteristics, migration and metastasis, and chemotherapy sensitivities of human cancers. We further investigated the potential genetic and epigenetic regulation of GPX3 in cancer. Our results suggested that GPX3 plays a complicated role in the tumor microenvironment, simultaneously promoting metastasis and chemotherapy resistance in human cancers.